Answer:
see explanation
Explanation:
The standard form of a quadratic equation is
ax² + bx + c = 0 : a ≠ 0
Express the equations in this form and extract the coefficients
1
4 - 2x + 3x² = 0 , that is
3x² - 2x + 4 = 0 ← in standard form
with a = 3, b = - 2 and c = 4
2
x(x + 5) - 2x = 0 ← distribute parenthesis
x² + 5x - 2x = 0
x² + 3x = 0 ← in standard form
with a = 1, b = 3 and c = 0
3
x² - 2x(x - 2) + 5 = 0 ← distribute parenthesis and simplify
x² - 2x² + 4x + 5 = 0
- x² + 4x + 5 = 0 ← in standard form
with a = - 1, b = 4 and c = 5